11.4k views
5 votes
Try it Solve the equation. If necessary 2-4x= -9x+ 2 3 7 + 2 5 = +- 6 Combine Terms Apply properties: Add Subtract Multiply Divide To start over: Reset

User Taherh
by
5.3k points

1 Answer

4 votes

(2)/(3)-4x+(7)/(2)=-9x+(5)/(6)

We apply associative property to rearrange:


-4x+(7)/(2)+(2)/(3)=-9x+(5)/(6)

We solve the sum of similar terms:


-4x+(7)/(2)+(2)/(3)=-9x+(5)/(6)
-4x+(25)/(6)=-9x+(5)/(6)

We add 9x to both sides (to cancel -9x):


-4x+9x+(25)/(6)=-9x+9x+(5)/(6)
5x+(25)/(6)=(5)/(6)

We subtract 25/6 both sides (to cancel 25/6):


5x+(25)/(6)-(25)/(6)=(5)/(6)-(25)/(6)


5x=(-20)/(6)

We divide by 5 both sides (to cancel 5):


(5x)/(5)=(-20)/(6\cdot5)
x=(-20)/(30)

Finally we simplify the fraction:


x=(-20)/(30)=(-4)/(6)=(-2)/(3)

User Kralizek
by
5.0k points